(untitled) (Bioscience Journal, 2021)
Cervical cancer is the second type of cancer that most affects women, considered a serious public health problem, however it can be detected and treated early through the Pap smear. This research aimed to analyze the knowledge, attitude and practices of biomedicine students on the Pap smear. A cross-sectional study on Knowledge, Attitude and Practice (KAP), applied with 108 students, was carried out at a Higher Education Institution in Teresina, Piauí, Brazil. The data were collected through the months of February and March of 2018 with the application of a questionnaire. Statistical analysis was descriptive in terms of absolute and relative frequencies. Knowledge 72 (66.6%) and attitude 76 (70.3%) presented adequate levels regarding the examination. As for the practice, the percentage of suitability was of 37 academics (34.2%) relatively not adequate. It was concluded that the students had adequate knowledge and attitude, but an inadequate practice, and the Papanicolaou test is required for the early screening and prevention of cervical cancer.